Processus morphodynamiques et sédimentaires dans les mangroves en érosion de Mayotte, océan Indien - Matthieu Jeanson; Franck Dolique; Edward J. Anthony (VertigO, 2018)
The Island of Mayotte, in the Indian Ocean, is characterized by a highly diversified shoreline comprising numerous mangrove zones set within a vast coral reef and lagoon complex. Many of these mangroves show a clear regression with significant geomorphological implications. Field experiments were conducted in order to document beach morphological changes and to determine hydro-sedimentary processes. Hydrodynamic measurements showed the marked effect of the mangrove vegetation distribution on wave energy attenuation. In mangrove areas, wave energy reduction reaches over 90 %, compared to 35 % in mangrove-free areas. Morphological observations have shown that the mangrove retreat is accompanied by erosion of the muddy-sandy substrate by waves which rework and concentrate the sand into well-defined bars, whereas the mud is dispersed towards the lagoon. The sand bars progressively migrate shoreward as swash bars that are built up into beach ridges by waves behind the subsisting mangrove fringe. Continuous beach ridge accretion leads to burial and asphyxia of mangrove root systems, further leading to mangrove mortality. This study highlights the role of mangroves, which exert significant control on the activation of coastal geomorphic processes and intertidal sedimentation. These processes perfectly reflect the notion of biogeomorphological adjustments inherent in these coastal systems.